The Status of School Psychology in Ontario School Boards: 2016 Perspective. (September 2016) - Lean, Debra
This article reports on the status of school psychology in Ontario. School psychology practice in Ontario has continued to evolve since the previous report was published in 2001. School psychologists have varied roles, and although the most prominent one remains as assessing students for entry into certain special education services, school-based psychology services in Ontario serve an advantageous role for district school boards as they offer all levels of service. As such, school psychologists are providing more mental health awareness, prevention, and intervention services than previously reported. Since 2013, every school board has a Mental Health Lead, and each district school board is required to produce a School Mental Health Strategy. The current five levels of service/intervention, registration requirements, and training opportunities as well as professional organizations for school psychologists are further discussed in the present report.